Depression and anxiety in patients receiving interferon-alpha: The role of illness perceptions. (September 2018) - Hepgul, Nilay; Pariante, Carmine M; Baraldi, Sara; Borsini, Alessandra; Bufalino, Chiara; Russell, Alice; Agarwal, Kosh; Cleare, Anthony J; Forton, Daniel M; Henderson, Max; Mondelli, Valeria; Ranjith, Gopinath; et al.
Development of psychiatric symptoms during interferon-alpha therapy may be influenced by psychological factors. We examined illness perceptions using the Revised Illness Perceptions Questionnaire in 55 patients with chronic hepatitis C virus infection, due to receive interferon-alpha. The Hospital Anxiety and Depression Scale was used to assess the development of symptoms. Negative identity, consequences and emotional representation beliefs were significantly associated with both higher depression and anxiety scores. Negative illness perceptions play a predictive role in the development of interferon-alpha-induced psychiatric symptoms.